Implementasi Program Kegiatan Rohani Islam dalam Membantu Pembentukan Karakter Religius Peserta Didik di SMP Negeri 1 Baleendah Kabupaten Bandung - Kusnandar, Nandar; Tafsir, Ahmad; Sukandar, Ahmad (CV. Media Publikasi Profesional, 2021)
In recent years, Islamic religious education has had problems, including religious education which has become a sharp focus of society. The number of deviant behavior of students and adolescents in general that is not in accordance with religious norms has recently prompted various parties to question the effectiveness of the implementation of religious education in schools. Seeing these problems, it is necessary to have several breakthroughs, one of which can be done through the cultivation of religious characters from an early age which is applied in schools both through classroom learning and other activities such as religious extracurricular activities. Religious extracurricular which is now called Rohis has an important role in the process of forming religious character for students. This research was conducted at SMPN 1 Baleendah which aims to find out (1) the planning of the Rohis extracurricular program at school, (2) the implementation of the Rohis extracurricular in an effort to form the religious character of students at school, (3) Evaluation of the implementation of the Rohis extracurricular on the formation of the religious character of the students. at school. This research uses qualitative research with a case study approach. The study used 3 data collection techniques, namely: observation, interviews and documentation. The analysis in this study uses interactive data analysis from Miles and Huberman with the stages of data collection, data collection, data presentation, drawing conclusions and checking the validity of the data. The results of the research show (1) The planning of the Rohis extracurricular program aims to shape the religious character of students. The spiritual extracurricular program planning includes the making of Competency Standards, Activity Programs, Activity Schedules, and Program implementation strategies (2) The Spiritual extracurricular implementation is carried out with four types of activities, namely daily, weekly, annual and incidental. Efforts are made by providing tausiah, exemplary attitudes, and habituation in activities at school. (3) Evaluation of the implementation of extracurricular Rohis can be seen from the extent of religious knowledge and behavior of participants listed in the student learning outcomes book. While the impact of extracurricular Rohis in SMPN 1 Baleendah has a positive impact, namely it can help students more easily appreciate Islamic religious values ​​and help suppress juvenile delinquency and bad influence on the character of students.